The complete chloroplast genome sequence of Neopallasia pectinata (Asteraceae) - Yu, Jingya (Mitochondrial DNA B Resour, 2021)
The complete chloroplast (cp) genome of Neopallasia pectinata was sequenced and analyzed in this study. It was 150,766 bp in length and has a typical circular structure, including a large single copy (LSC) with 82,605 bp, two inverted repeats (IRs) with 24,944 bp, and a small single copy (SSC) with 18,273 bp. The phylogenetic analysis of N. pectinata and its related taxa was conducted depended on the complete cp-genome sequences. The maximum likelihood tree indicates a close relationship between Chrysanthemum and Neopallasia. The cp-genome of N. pectinata is useful for future phylogenetic studies of Asteraceae.